Real-time active noise control with preservation of desired sound. (1st January 2020) - Zhou, C.; Utyuzhnikov, S.
Abstract: In the active sound control problem a quite arbitrary bounded domain is shielded from noise generated outside by implementing secondary sound sources on the perimeter. The sound generated by interior sources, also known as desired sound, is supposed to be protected inside the shielded domain. If the desired sound is present, it is required to remain it unaffected by the control. This problem becomes much more complicated since the secondary sources have a reverse effect on the input data. In the current paper, a novel potential-based algorithm for active sound control is applied to attenuate noise with the preservation of desired sound. The uniqueness of this algorithm is that it realizes an active sound control via the utilization of surface potentials which have a projection property. The algorithm automatically removes the contribution of controls and desired sound from the total input field to be measured. The applicability of the algorithm is demonstrated via a series of numerical experiments. In addition, some factors such as the effect of the number of controls and sensors are also discussed.